The Effect Of Fermentation On Nutrition Content (Protein, Fat, Carbohydrate And Fiber) In Processed Red Beans (Phaseolus Vulgaris L.) - Erwin Indayanti; Sugeng Maryanto; Purbowati (JURNAL GIZI DAN KESEHATAN, 2021)
Red bean tempeh is a processed product from nuts which is formed by the help of Rhizopus sp, mold through a fermentation process. One of the uses of red bean production through the boiling and fermentation process is an effort to increase the variety of red bean processing to increase the nutritional value of kidney beans. Purpose To determine the nutritional content and analysis of nutritional content in boiled red beans and red bean tempeh. This study was a pre experimental design. With a completely randomized design approach. The research carried out is by making preparations in the form of boiled red beans and red bean tempeh and then tested for nutritional content. The analysis test for protein content used the kjedahl method, the fat content used the Soxhlet method, the carbohydrate content used the anthrone method, and the fiber content used the reflux method. Statistical analysis of different tests was performed using the independent t test, with data distribution normally distributed. The average yield of nutrient content in boiled red beans was 18.77% protein, 4.03% fat, 27.40% carbohydrates, and 18.25% fiber. The nutritional content of red bean tempeh is 12.26% protein, 3.96% fat, 34.75% highest carbohydrate, and 22.10% fiber. The most significant test results were the carbohydrate content (p = 0.001) and the protein content (p = 0.021). Fat (p = 0.965) and fiber (p = 0.399) content showed no significant difference. There are differences in the nutritional content of boiled red beans and red bean tempeh, namely in the carbohydrate content and protein content, which shows a significant difference (p <0.05).